DESKRIPSI PENILAIAN MASYARAKAT TENTANG DAMPAK PERKEMBANGAN KAWASAN TERBANGUN BERDASARKAN PERTIMBANGAN MULTI ASPEK DI KOTA YOGYAKARTA - apriani, ani (Sekolah Tinggi Teknologi Adisutjipto, 2018)
The increasing of development in Yogyakarta City gives rise to controversy. Physical development-oriented activities tend to pursue economic benefits with less regard for social and environmental impacts. The purpose of this paper will describe the communitys assessment of the impact of regional development on environmental, socio-cultural and economic aspects. This research uses quantitative descriptive approach as the method. The perception of negative impact from built-up area development to the environmental aspect was represented by 128 people (32,0%) while no negative impact perception was represented by 272 people (68%). The perception of negative impact from built-up area development to the socio-cultural aspect was stated by the 83 respondents (20.8%) and 317 respondents (79.2%) presented no negative impact. Meanwhile, in the economic aspect, the perception of negative impact from built-up area developmment was expressed by 147 respondents (36.8%) and 253 respondents (63.2%) presented no negative impact.Â Keyword: Impact, City, Development, Community, Perseption.